Strategi branding untuk instansi pendidikan dasar - Lestari, Arrum Puji; Musbikhah, Sabitatul; Purnomo, Riki Ahmat; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
The branding strategy approach has become the focus of attention in efforts to improve the quality of basic education. The research aims to apply strategies in the context of basic education institutions to improve teaching effectiveness and educational quality. It is known that basic education insitutions can adopr some of the best practices that have been discovered, including the use of technology in learning, parental involvement and the development of relavant curricula. Implementation of these practices has resulted in significant improvements in student achievement, learning motivation, and teaching quality. However, challenges faced in adopting these practices were also identified, including the need for adequate resources and support from all relevant interests. Therefore, recommendations and follow-up steps are suggested to ensure successful implementation of best practies in the basic education context.